(untitled) (Journal of Comparative Social Work, 2014)
This article discusses the significance of gender in the encounter between an injured body and cultural discourses. When young women who self-harm present bodies that deviate from the norms for what female bodies should look like, they face sanctions. Young women who injure their own bodies are affected by social discourses about expectations for women and women’s bodies, which in turn affect their gender identities. This article builds on interviews with 12 young women who injure or have injured their own bodies